Development of a Potential Prebiotic Film Based on Sago Flour and Kepok Plantain Peel Starch with Prebiotic Properties to Support Lactobacillus plantarum Growth - Miksusanti; Rennie Puspa Novita; Rizki Palupi; Syaflina Lamin; Eliza; Rizkika Amelia; Daniel Alfarado (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Innovative prebiotic carriers that can be directly integrated into foods are increasingly sought for functional food development. This study developed prebiotic starch films using sago flour and starch from kepok plantain (Musa paradisiaca) peel, designed as intrinsic prebiotic components rather than packaging. Films were formulated with 1%, 3%, and 5% plantain peel starch and characterized for physicochemical properties, morphology, and their prebiotic effect on Lactobacillus plantarum. Higher starch concentrations increased film thickness (0.13–0.18 mm) and moisture content (11.42–16.24%), while significantly decreasing water solubility (55.31–41.14%) (p < 0.05). Tensile strength was low (0.17–0.27MPa) and elongation high (89.28–178.10%). FTIR confirmed polysaccharide functional groups; SEM revealed heterogeneous fibrous structures. Resistant starch in films (1.89–3.76%) was lower than raw starch (38.91%) due to gelatinization. The 5% starch film supported the highest L. plantarum viability (26 × 108 CFU/mL), compared to 3% (23 × 108 CFU/mL) and 1% (21 × 108 CFU/mL), demonstrating that plantain peel starch acts as an effective intrinsic prebiotic without commercial prebiotics. The composite film shows potential as active packaging or a probiotic carrier in functional foods, although mechanical and water barrier optimization is still required.